Analyzing hedyotis diffusa mechanisms of action from the genomics perspective. (June 2019) - Hu, Chen-Jun; He, Ju; Li, Guo-Zheng; Fang, Pei-Pei; Xie, Jia-Dong; Ding, You-Wei; Mao, Yu-Qing; Hu, Kong-Fa
Highlights: Analyzing hedyotis diffusa from the genomics perspective. A total of 17, 930 proteins are used in this study. Discover unknown signaling pathways that an herb could possibly affect. Abstract: Background and objective: Hedyotis diffusa is an herb used for anti-cancer, anti-oxidant, anti-inflammatory, and anti-fibroblast treatment in the clinical practice of Traditional Chinese Medicine. However, its pharmacological mechanisms have not been fully established and there is a lack of modern scientific verification. One of the best ways to further understand Hedyotis diffusa's mechanisms of action is to analyze it from the genomics perspective. Methods: In this study, we used network pharmacology approaches to infer the herb-gene interactions, the herb-pathway interactions, and the gene families. We then analyzed Hedyotis diffusa's mechanisms of action using the genomics context combined with the Traditional Chinese Medicine clinical practice and the pharmacological research. Results: The results obtained in the pathway and gene family analysis were consistent with the Traditional Chinese Medicine clinical experience and the pharmacological activities of Hedyotis diffusa. Conclusions: Our approach can identify related genes and pathways correctly with little a priori knowledge, and provide potential directions to facilitate further research.